Human Gingiva-Derived Mesenchymal Stem Cells Modulate Monocytes/Macrophages and Alleviate Atherosclerosis - Zhang, Ximei; Huang, Feng; Li, Weixuan; Dang, Jun-long; Yuan, Jia; Wang, Julie; Zeng, Dong-Lan; Sun, Can-Xing; Liu, Yan-Ying; Ao, Qian; Tan, Hongmei; Su, Wenru; et al. (Frontiers in Immunology, 2018)
Atherosclerosis is the major cause of cardiovascular diseases. Current evidence indicate that inflammation is involved in the pathogenesis of atherosclerosis. Human gingiva-derived mesenchymal stem cells (GMSC) have shown anti-inflammatory and immunomodulatory effects on autoimmune and inflammatory diseases. However, the function of GMSC in controlling atherosclerosis is far from clear. The present study is aimed to elucidate the role of GMSC in atherosclerosis, examining the inhibition of GMSC on macrophage foam cell formation and further determining whether GMSC could affect the polarization and activation of macrophages under different conditions. The results show that infusion of GMSC to AopE-/- mice significantly reduced the frequency of inflammatory monocytes/macrophages and decreased the plaque size and lipid deposition. Additionally, GMSC markedly inhibited macrophage foam cell formation and reduced inflammatory macrophage activation, converting inflammatory macrophages to anti-inflammatory macrophages in vitro. Thus, our study has revealed a significant role of GMSC on modulating inflammatory monocytes/macrophages and alleviating atherosclerosis.